ANALISIS PERSEPSI NASABAH TERHADAP PENERAPAN SISTEM LAYANAN JASA E-BANKING PADA PT. BANK NEGARA INDONESIA CABANG PONTIANAK - B31110031, ENTIN KARTINI (Jurnal Manajemen Update, 2015)
This study entitled "Perception Analysis Of Customers On System Implementation Of E-Banking Services at PT. Bank Negara Indonesia Cabang Pontianak". This study aims to determine customer perception or assessment of the implementation of E-banking services at PT. Bank Negara Indonesia Pontianak Branch. Forms of research is survey studies, which will be done by collecting data from respondents who are customers of the PT. Bank Negara Indonesia Cabang Pontianak. The method used is descriptive qualitative method. The variables used to determine customers  perception  for  E-Banking  service  at  PT.  Bank  Negara  Indonesia  Cabang Pontianak are Usability (Usability), Usefulness of Content (Benefits of Contents), Adequacy of Information (Adequacy of information), and Interaction (interaction). The results show the average score for Usability variable is equal to 211, the variable Adequacy of Information at 207, Interaction variables at 203 and variables Usefulness of Content at 202. It can be concluded that customer perception of the service E-Banking is implemented by Bank Negara Indonesia is good, indicating generally satisfied customer and the bank has managed to provide maximum service and ease of doing financial transactions.   Keywords: Customer Perception, E-Banking Services.